2017
DOI: 10.1158/2159-8290.cd-17-0797
|View full text |Cite
|
Sign up to set email alerts
|

Found in Translation: How Preclinical Research Is Guiding the Clinical Development of the BCL2-Selective Inhibitor Venetoclax

Abstract: Since the discovery of apoptosis as a form of programmed cell death, targeting the apoptosis pathway to induce cancer cell death has been a high priority goal for cancer therapy. After decades of effort, drug discovery scientists have succeeded in generating small-molecule inhibitors of antiapoptotic BCL-2 family proteins. Innovative medicinal chemistry and structure-based drug design, coupled with a strong fundamental understanding of BCL-2 biology, were essential to the development of BH3 mimetics such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
83
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 168 publications
(179 reference statements)
1
83
0
1
Order By: Relevance
“…Previous work showed that MYC activation sensitized cells to tigecycline and that treatment with this antibiotic retarded the progression of MYC-driven lymphomas in mice (16,17). Here, we followed up on these findings to assess the activity of tigecycline against DHL, in combination with the BCL2 inhibitor venetoclax (8)(9)(10). We first showed that overexpression of BCL2 in mouse E-myc lymphomas blocked tigecycline-induced cell death, which was restored upon The antitumoral activity of tigecycline in either mouse or human cells is attributed to its inhibitory activity on mitochondrial translation and, as a consequence, on oxidative phosphorylation (16,18,(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous work showed that MYC activation sensitized cells to tigecycline and that treatment with this antibiotic retarded the progression of MYC-driven lymphomas in mice (16,17). Here, we followed up on these findings to assess the activity of tigecycline against DHL, in combination with the BCL2 inhibitor venetoclax (8)(9)(10). We first showed that overexpression of BCL2 in mouse E-myc lymphomas blocked tigecycline-induced cell death, which was restored upon The antitumoral activity of tigecycline in either mouse or human cells is attributed to its inhibitory activity on mitochondrial translation and, as a consequence, on oxidative phosphorylation (16,18,(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 94%
“…In both groups, activation of MYC and BCL2 correlates with poor prognosis in the face of current front-line treatments, including combined immunotherapy and chemotherapy [such as rituximab and CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) chemotherapy, or R-CHOP] (1-7), calling for the development of new therapeutic regimens. A most promising prospect in this regard is the emergence of selective BCL2 inhibitors, such as venetoclax (also called ABT-199) (3,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…19 However, the mere expression of BCL-2 does not necessarily imply dependence, and any of the other suppressors can potentially drive leukemogenesis. 8 In fact, although the 5 antiapoptotic proteins share homology in 1 or more BH domains, some proapoptotic proteins share homology only in the BH3 domain and have specific interactions with these 5 proteins ( Figure 1B). As a consequence, by exposing mitochondria to known concentrations of BH3 peptides and measuring the resulting permeabilization of the outer mitochondrial membrane, it is possible to understand on what specific antiapoptotic proteins a cell is dependent for survival.…”
Section: Introductionmentioning
confidence: 97%
“…The BCL-2 family proteins' roles can be divided into 4 main functions: suppressors (BCL-2, BCL-XL, BCL-W, BCL2-A1, and MCL-1), activators (BIM and PUMA), effectors (BAX and BAK), and sensitizers (NOXA). 8,9 Suppressors inhibit the activity of activators and effectors, preventing apoptosis, whereas sensitizers inhibit suppressors, releasing the brake on activators and effectors. The latter oligomerize, creating…”
mentioning
confidence: 99%
“…This kind of therapy could be accomplished by enhancing physiological apoptotic pathways in dysfunctional neurons, for example through targeting the anti-apoptotic factors B cell leukemia/lymphoma 2 (Bcl-2) or Bcl-xL. In fact, translational medicine testing smallmolecule drugs that mimic the BH3-only protein effect to selectively inhibit Bcl-2 and kill cancer cells has achieved notable success in the treatment of hematopoietic tumors (Leverson et al, 2017;Merino et al, 2018). As an alternative, induction of the cell competition machinery described above to removal unfit neurons may have strikingly beneficial effects.…”
Section: Discussionmentioning
confidence: 99%